2011
DOI: 10.1007/s10551-011-1158-5
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Emotional Intelligence on the Ethical Judgment of Managers

Abstract: In recent years there has been a substantial amount of research on emotional intelligence (EI) across a wide range of disciplines. Also, this term has been receiving increasing attention in the popular business press. This article extends previous research by seeking to determine whether there is a relationship between emotional intelligence and ethical judgment among practicing managers with respect to questions of ethical nature that can arise in their professional activity. It analyzes the results of a surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 66 publications
2
47
0
Order By: Relevance
“…Idealism and relativism have been demonstrated to have significant effects on consumers' ethical beliefs (Vitell and Paolillo 2003). Angelidis and Ibrahim (2011) demonstrate that emotional intelligence is related to ethical ideologies (typologies based on the combination of high/low idealism and high/low relativism). In particular, situationists (those with high levels of idealism and relativism) have relatively high emotional intelligence.…”
Section: The Mediating Role Of Personal Moral Philosophiesmentioning
confidence: 92%
See 3 more Smart Citations
“…Idealism and relativism have been demonstrated to have significant effects on consumers' ethical beliefs (Vitell and Paolillo 2003). Angelidis and Ibrahim (2011) demonstrate that emotional intelligence is related to ethical ideologies (typologies based on the combination of high/low idealism and high/low relativism). In particular, situationists (those with high levels of idealism and relativism) have relatively high emotional intelligence.…”
Section: The Mediating Role Of Personal Moral Philosophiesmentioning
confidence: 92%
“…These scales have been used extensively in business ethics research (e.g. Angelidis andIbrahim 2011, Singhapakdi et al 1999, etc.). Similar to Angelidis and Ibrahim (2011), who used these measures to examine the relationship between emotional intelligence and personal moral philosophies and Rawwas et al (2005) who used these measures to investigate the relationship between personal moral philosophies and consumer ethics, a five-point Likert scale (1 being 'strongly disagree' to 5 being 'strongly agree') was used to measure agreement with each item.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Students with higher EI were reported to perform better than staff nurses(Schenk & Harper, 2014). In the study conducted among nursing Interns, Internet addiction levels were lower among students with higher level of EI (Angelidis & Ibrahim, 2011). Prior literature indicated that emotional intelligence (EI) is a significant indicator of future achievement in every walk of life, as well as academic achievement, and career success among university students (Saarni, 1999;Goleman 1995 A recent systemic review revealed the fact that higher EI is significantly related to better academic success among university students (Hanafi and Noor, 2016).…”
Section: Ei and Performancementioning
confidence: 99%